Dynamics of a Predator–Prey System with Wind Effect and Prey Refuge - Takyi, Eric M.; Cooper, Kasey; Dreher, Ava; McCrorey, Caroline (Journal of Applied Nonlinear Dynamics, 2026)
The natural environment of living organisms is not only affected by biotic factors but also by abiotic factors, including omnipresent wind. There has been less exploration on the effects of both biotic and abiotic factors on the dynamics of predator-prey interactions. In this work, we propose and study the dynamics of a predator-prey system incorporating wind effects and prey refuge. A refuge can be described as any strategy to avoid or reduce predation risks. We first prove positivity and boundedness of solutions for the system. We analyze the existence of equilibria under certain parametric restrictions. We also derive sufficient conditions for the global stability of the coexistence equilibrium using a suitable Lyapunov functional. Further dynamical analysis reveals that the system experiences local codimension one bifurcations including Hopf and transcritical bifurcations. Our findings show that when prey refuge is in use, it has a stabilizing effect on the system and also increases the equilibrium density of the prey population while the predator equilibrium density decreases. We also observe that the strength of wind flow has both stabilizing and destabilizing effects. We support our theoretical findings with numerical experiments and give their ecological implications.